Imaging and identification of point defects in PtTe2 - Zhussupbekova, Ainur; Duesberg, Georg; Shvets, Igor (My University, 2021)
The properties and performance of two-dimensional (2D) materials can be greatly affected by point defects. PtTe2, a 2D material that belongs to the group 10 transition metal dichalcogenides, is a type-II Dirac semimetal, which has gained a lot of attention recently due to its potential for applications in catalysis, photonics, and spintronics. Here, we provide an experimental and theoretical investigation of point defects on and near the surface of PtTe2. Using scanning tunneling microscopy and scanning tunneling spectroscopy (STS) measurements, in combination with first-principle calculations, we identify and characterize five common surface and subsurface point defects. The influence of these defects on the electronic structure of PtTe2 is explored in detail through grid STS measurements and complementary density functional theory calculations. We believe these findings will be of significance to future efforts to engineer point defects in PtTe2, which is an interesting and enticing approach to tune the chargecarrier mobility and electron–hole recombination rates, as well as the site reactivity for catalysis.
PUBLISHED
Keywords: Scanning tunneling microscopy, point defects, transitional metal dichalcogenides; Nanoscience & Materials; NANOSTRUCTURES; Nanotechnology; SEMICONDUCTOR DEVICES AND MATERIALS